POCIS Calibration for Organic Compound Sampling in Small Headwater Streams. (4th June 2020) - Booij, Kees; Chen, Sunmao; Trask, Jennifer R.
Abstract: Field‐based atrazine sampling rates ( R s ) obtained by the polar organic chemical integrative sampler (POCIS) method were measured in 9 headwater streams over 3 yr covering 5 to 6 exposure periods of 2 to 3 wk/site/yr. Rates were best in line with the model R s = 148 mL/d, with a standard deviation of 0.17 log units (factor 1.5). The POCIS canisters reduced mass transfer coefficients of the water boundary layer by a factor of 2 as measured by alabaster dissolution rates. A mechanistic model that accounts for flow and temperature effects yielded a fair estimate of the effective exchange surface area (12.5 ± 0.8 cm 2 ). This model could only be tested for higher flow velocities because of uncertainties associated with the measurement of flow velocities <1 cm/s. Pictures of sorbent distributions in POCIS devices showed that the effective exchange surface area varied with time during the exposures. Error analysis indicated that sorbent distributions and chemical analysis were minor error sources. Our main conclusion is that an atrazine sampling rate of 148 mL/d yielded consistent results for all 3 yr across 9 headwater streams. Environ Toxicol Chem 2020;39:1334–1342. © 2020 SETAC Abstract : Polar organic chemical integrative sampler (POCIS)‐based atrazine aqueous concentrations ( C w ) were consistent with concentrations from daily composite water sampling in 9 headwater streams over 3 yr.